Identifying Changes of Brain Regional Homogeneity and Cingulo-Opercular Network Connectivity in First-Episode, Drug-Naïve Depressive Patients With Suicidal Ideation - He, Mengxin; Ping, Liangliang; Chu, Zhaosong; Zeng, Chunqiang; Shen, Zonglin; Xu, Xiufeng (Frontiers in Neuroscience, 2022)
Objective: Adult patients with major depressive disorder (MDD) may not actively reveal their suicidal ideation (SI). Therefore, this study is committed to finding the alterations in the cingulo-opercular network (CON) that are closely related to SI with Multi-imaging methods, thus providing neuroimaging basis for SI. Method: 198 participants (129 MDD patients, 69 healthy controls) were recruited and evaluated with the Montgomery–Asberg Depression Rating Scale (MADRS). The healthy individuals formed the HC group, while the MDD patients were subdivided into No SI MDD (NSI, n = 32), Mild SI MDD (MSI, n = 64), Severe SI MDD (SSI, n = 33) according to their MADRS item 10. We obtained MRI data of all participants and applied regional homogeneity (ReHo) analysis to verify a previous finding that links CON abnormality to SI. In addition, we employed the SCN analysis to investigate the correlation between abnormal structural connectivity of CON and SI severity. Results: Compared to those of the HC group, MDD ReHo values and GMV were consistently found abnormal in CON. ReHo values and GMV of the right orbital inferior frontal gyrus (ORBinf.R) in the MDD group decreased with the increase of SI. Compared to the HC group, the MDD patients showed enhanced structural connectivity of three pairs of brain regions in CON (ACC.L - left superior frontal gyrus (SFG.L), SFG.L- left middle temporal gyrus (MTG.L), and the SFG.L-left postcentral gyrus (PoCG.L)). Compared with NSI, MSI groups, the structural connectivity of three pairs of brain regions in CON is enhanced in the SSI groups (ORBinf.L - right ventral posterior cingulate gyrus(VPCC. R), VPCC. R - SFG.R and SFG.R-PoCG.R). Conclusions: Our findings showed the distinctive ReHo, GMV, and SCN pattern of CON in MDD patients with SI, and with the severity of suicide, abnormal brain regions increased. Our finding suggested MDD patients with different severity of suicidal ideation have different neuroimaging changes.